Moda a vapor: influências do estilo steampunk - Lima, Jessica Sala de (2015)
This paper aims to show aspects of steampunk that this is an urban culture which is based on retrôfuturismo, glancing in the past and imagining a future that has not happened in this past, steampunk has emerged as a literary genre of science fiction set in the nineteenth century and grew in order to achieve other means of expression is also entering in the fashion world. It comes after synthesis of ideas, a brand aimed at the public steamer, with a collection of casual clothes containing the visual language of steampunk.